Effects of electrode size on basic excitatory responses and selected electric stimulator parameters - Kantor, Gideon; Alon, Gad; Ho, Henry S. (IEEE Engineering in Medicine and Biology 14th Annual Conference, 1992, 1992)
This electrical stimulation study investigates the effects of electrode size on the basic excitatory responses of four healthy Subjects. Four different sizes of self-adhesive surface electrodes from (2.25 cm 2 ) to (40.3 cm 2 ) were applied over the medial and lateral gastrocnemius muscles. The excitatory levels considered were sensory threshold (ST), motor threshold (MT), pain threshold (PT) and maximally tolerated painful (MP) stimulation. The stimulus was a symmetric biphasic waveform with 200 µSec phase duration and a repetition rate of 50 Hz. The amplitude of the stimulus was increased until the appropriate excitatory response was achieved, at which time the computerized system recorded the peak voltage and peak current and computed the associated phase charge. The data showed that for all dependent variables tested the largest electrode (40.3 cm 2 ) required about 40 percent lower peak voltage and 400 percent higher peak current compared to the smallest electrode (2.25 cm 2 ). The ratio of the peak voltage to the peak current decreased non-linearly as electrode size increased. The data also showed that phase charge increased 700 percent and phase charge density (phase charge divided by electrode surface) decreased 60 percent as electrode size increased. The peak currents and phase charges that elicit a painful response were much lower as the electrode size became smaller. We concluded that electrode size effects are non-linearly related to the stimulus parameters required for inducing common excitatory responses. This information could be very useful in the development of a load simulating the electrode-tissue interface for different types of electrodes.